Słuchowisko eksperymentalne w świetle realizacji Studia Teatralnych Form Eksperymentalnych i projektów Nowe Słuchowiska - Kowalska-Elkader, Natalia (Zagadnienia Rodzajów Literackich, 2021)
The main aim of this publication ist to identify, classify and describe radio dramas that were made for Studio Eksperymentalnych Form Teatralnych (Experimental Drama Studio) and as a Nowe Słuchowiska/New Radio Dramas project. I will also provide a description of sound and voice materials of so-called experimental radio dramas. In the first part, the article explains the experimental radio drama genre. It shows the drama subgenres and determinants of experimental drama pattern. In the second part, the article is focused on broadcasts made by Studio Eksperymentalnych Form Teatralnych (Experimental Drama Studio) and in the project New Radio Dramas.